Reforming the agricultural extension system in India: What do we know about what works where and why? - Raabe, Katharina (International Food Policy Research Institute, 2008)
In order to realize agricultural potential and to increase agricultural yields, India's extension system has experienced major conceptual, structural, and institutional changes since the late 1990s. This paper reviews existing reform programs and strategies currently existing in agricultural extension in India. It distinguishes strategies that have been employed to strengthen both the supply and demand sides of service provision in the area of agricultural extension, and it reviews the effects of the demand- and supply-side strategies on the access to and the quality of agricultural extension services. The ultimate objectives are (1) to gain a view on what works where and why in improving the effectiveness of agricultural extension in a decentralized environment; (2) to identify measures that strengthen and improve agricultural extension service provision; and (3) to reveal existing knowledge gaps. Although the range of extension reform approaches is wide, this paper shows that an answer to the question of what works where and why is complicated by the absence of sound and comprehensive qualitative and quantitative impact and evaluation assessment studies. Even evidence from the National Agricultural Technology Project and the Diversified Agricultural Support Project of the World Bank, the women empowerment programs of the Danish International Development Agency, the Andhra Pradesh Tribal Development Project, and the e-Choupal program of the Indian Tobacco Company is subject to methodological and identification problems. Conclusions regarding the importance (1) of implementing both decentralized, participatory, adaptive, and pluralistic demand- and supply-side extension approaches; (2) of involving the public, private, and third (civil society) sectors in extension service provision and funding; and (3) of strengthening the capacity of and the collaboration between farmers, researchers, and extension workers are necessarily tentative and require further quantification. The paper seeks to inform policymakers and providers of extension services from all sectors about the need to make performance assessments and impact evaluations inherent components of any extension program so as to increase the effectiveness of extension service reforms.